Digital legal culture: Developing the concept of legal culture in the era of social media from a sociological law perspective - Deden Sidiq Sholehudin (Education of Law Journal, 2025)
The digital era has fundamentally transformed the way legal norms are disseminated, interpreted, and internalized in society. Despite the growing importance of digital communication in shaping legal awareness and behavior, there remains a significant research gap in the sociological study of legal culture, particularly regarding how social media alters the production and perception of law. This study addresses that gap by analyzing the influence of social media on legal awareness and behavior, identifying shifts in legal values under the dominance of digital space, and developing the concept of Digital Legal Culture as a theoretical expansion of Lawrence M. Friedman’s legal system theory. Using an exploratory qualitative approach supported by netnography and literature review, this research investigates the transformation of legal culture in the digital age. Findings reveal that social media not only democratizes access to legal knowledge, but also decentralizes legal authority, enabling online communities and influencers to co-construct legal meanings. This results in a participatory, global, and dynamic form of legal culture, marked by phenomena such as "No Viral, No Justice" and the emergence of algorithmic legitimacy. This study contributes a novel conceptual framework, Digital Legal Culture, defined as the values, attitudes, and beliefs towards law that are constructed, contested, and disseminated within digital interaction spaces. The findings offer theoretical and practical insights for scholars and policymakers aiming to enhance legal literacy, reinforce institutional credibility, and ensure justice in an increasingly digitized society.